Immunological Consequences of Infertility: From Immune Basis to Immunotherapy for Miscarriage and Infertility - Kalmatov, Roman; Rahim, Fakher; Zhainagul Abdirasulovna, Abdirasulova; Gozin, Shamim; Rakhima Momunovna, Azhimamatova; Aizhan Nurlanovna, Omorova (Trends in Immunotherapy, 2025)
One of the causes of infertility and recurrent miscarriage is immunological factors or factors related to the immune system. Several immunological issues, for instance autoantibodies and alterations in the level of uterine immune cells, play a crucial role in immune-related infertility. This review evaluated all available immunological bases in female reproductive disorders, especially infertility and miscarriage to provide optimal diagnostic strategies for patients. NK cells are considered important elements of the innate immune system, ensuring that there is tolerance between the mother and child’s immune systems. Touching on the adaptive immune system, Th cells not only are able to impart directional structure on incoming lymphocytes draining from the periphery but also categorize into different subsets depending on where they are located within peripheral blood. During pregnancy, the immune system is skewed toward a type 2 T helper response, while fetal rejection is associated with a type 1 response The rules of organ transplantation require that the host’s immunological mechanisms, based on the incompatibility of antigens of the histocompatibility system, recognize the transplanted piece and ultimately reject it. Among the various therapeutic options, lymphocyte immunotherapy (LIT) stands out as a promising solution based on immunological principles. Some studies have shown that the success rate of LIT is 69%, but other studies have shown that the success rate has increased to 80%. On the other hand, controlled clinical trials are needed to further investigate immunomodulatory therapeutic strategies to help treat this disorder. Therefore, further studies are needed to achieve standardized diagnostic and immunological therapeutic approaches to increase the effectiveness of therapeutic interventions and increase the success rate of assisted reproductive technology (ART) cycles in these women.